Uses of Therapeutic Laser in Pediatric Dentistry: Review of the Literature. Case Reports - Rosales B. M.E., Miguel A.; Torre D.M.E.P., Gabriela; Saavedra Ch. C.D., Lydia H.; Márquez P. MEP, Raúl; Ruiz R. M.I.C., Ma. del Socorro; Pozos G. D.C., Amaury de Jesús; Garrocho R. D.C., Arturo (Odovtos - International Journal of Dental Sciences, 2018)
The term "LASER" is an acronym for "Light Amplification by the Stimulated Emission of Radiation" (in Spanish "Amplificación de Luz por Emisión Estimulada de Radiación"). The use of laser technology in dentistry has had a constant evolution and development in the last 30 years. Two large groups of lasers should be distinguished: high-power or surgical and low-power or therapeutic. The most used in pediatric dentistry is the therapeutic or LLLT (or "soft"). The therapeutic laser is indicated for various anomalies such as hypersensitivity, gingivitis, herpes, paresthesias, trigeminal neuralgias, trismus, TMJ dysfunction, implants, activation of teeth whitening chemicals, among others. This article intends to perform an update of the applications of low power laser in the field of Pediatric Dentistry, as well as the presentation of 4 representative clinical cases.